Evolution of 40K in fruit collected in Malaysia by the determination of total potassium using neutron activation analysis. - Shafaei, M. A.; Saion, Elias; Wood, K.; Mohamed Kamari, Halimah; Kh. Rezaee,; Mehdipure, L. A. (Springer Netherlands, 2010)
Potassium is an extremely important major to element to the human body. Potassium in made up of three isotopes with abundances of 39K at 93.1%, 40K at 0.0118% and 41K at 6.88%. It is also very well known that 40K is to measure the single 1460.8 keV photon from beta-decay. However, this procedure requires a significant amount of sample and typical counting periods of at least a day in wellshielded germanium counting system. Another approach is to determination total potassium via neutron activation analysis using the well know 41K(n,c)42K(T1/2=12.8 h) reaction and then evaluate 40K using the usual activity equation A=kN. In our laboratory we have effectively used thermal and epithermal neutron flux for neutron activation analysis to determine potassium in fruits. Upward to 7–9 batches of samples, which each of batch is including 14 samples so can be analysed in 1 day using only gram quantities of material. In such way on can increase the output of determining 40K by at least on order of magnitude. Result of a detailed investigation optimization of the methodology,quality control and detection limits will be presented for reference material and various fruits samples.